(untitled) (Global Journal of Science Frontier Research, 2018)
Airlines are suffering from such competition. Service quality is typically defined regarding consumer satisfaction. The purpose of this paper is to provide a better understanding of how satisfaction level among passenger with Arik and Aero Airlines is and how its managers can improve their service quality. To reach to achieve this purpose, we have studied different models of service quality measurement and adopted Gronroos model as a comprehensive model, we developed and adopted it to encompass various aspects of airlines’ services. We inclusively inferred that passengers of Arik and Aero are not satisfied with the perceived services and it warns manager to focus on passengers’ expectations. Tangibles, assurance, responsiveness, reliability, empathy, image and technical quality are seven features of the model, and in all of them, passengers feel dissatisfied. Managers should treat employees, improve visual facilities and coordinate all people, departments, and organizations involved with the airline. Finally, with airline must measure passengers’ satisfaction and service quality seasonally to keep the services corresponded with customers’ opinions.